IMPLEMENTASI MANAJEMEN STRATEGI PENDIDIKAN DALAM PELIBATAN MASYARAKAT TERHADAP PENINGKATAN KUALITAS PENDIDIKAN DI MIN 2 KOTA BANDUNG - Muftiyyatul Ummah; Mulyawan Safwandy Nugraha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
21st-century education necessitates cooperative, collaborative learning, and mastery of information technology. To meet these challenges, madrasahs must enhance the quality of education by involving the community in planning, implementation, and monitoring programs. This research aims to explore the implementation of educational strategy management at MIN 2 Kota Bandung involving the community and its impact on improving educational quality. The research method used is a qualitative approach with a case study design. Data collection was conducted through observations and in-depth interviews with the madrasah principal, vice principal, madrasah committee, and community figures. The results indicate that MIN 2 Kota Bandung has successfully developed a clear vision and mission to enhance educational quality. The school collaborates with the community in formulating strategies including improving teaching quality, curriculum development, and enhancing educational facilities. Community participation is manifested through financial donations, book donations, and involvement in school activities. Moreover, community involvement in decision-making creates a sense of ownership and shared responsibility for their children's education. The research demonstrates that community involvement has a positive impact on improving educational quality at MIN 2 Kota Bandung. Financial support enables the improvement of educational facilities and resources, while participation in school activities enhances student motivation and academic achievement. The collaboration between the school and the community creates a conducive and supportive learning environment.